Analysis of Hydroelectric Power Plants in East Kalimantan, Indonesia - Achmad Prannata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to determine the amount of potential renewable energy sources of hydroelectric power plants that have been used to meet the electrical energy needs in East Kalimantan at this time, the amount of potential renewable energy sources of hydroelectric power plants that have not been used for electrical energy needs in East Kalimantan at this time, and the planning of electrical energy to provide electrical energy in the province of East Kalimantan in order to In this study, energy supply and demand in the province of East Kalimantan were analyzed using LEAP (Long-range Energy Alternative Planning system) models. Analyze the energy supply and demand over the next thirteen years using 2012 as the starting point. The linear regression methodology used to project energy demand interpolates historical data, activity, and energy intensity. According to the study's findings, just 1,509 MW of the province of East Kalimantan's potential hydropower sources—6976.14 MW—have been used up to this point. In 2025, the population is expected to rise by 6,167,359 people, increasing the demand for electricity from 17,546,970 MWh to 20,643,495 MWh. According to the national energy management's blueprint for the goal composition of the energy mix, hydropower capacity in 2025 would have been 23,961,414 MWh or 55.56% of the overall producing capacity of 43,129,583 MWh.